2014
DOI: 10.7567/jjap.53.092703
|View full text |Cite
|
Sign up to set email alerts
|

On two optomechanical effects of laser-induced electrostriction in dielectric liquids

Abstract: This paper presents electrostriction from the phenomenological perspective, and gives details on two mechanical effects arising from lasermatter interaction. Electrostriction is the tendency of materials to compress in the presence of a varying electric field. In this paper, the investigated materials are polar and nonpolar dielectric liquids. It is stressed that the dominant factor is the time evolution of the laser pulse, which causes tensile stresses and acoustic waves. The study is supported by experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Optoacoustic effects originate from the fact that the optical properties of a medium can change as a result of density variations, 62 which can trigger the generation of acoustic waves. [70][71][72][73][74][75][76] When radiation is strongly absorbed, as in the case of Terahertz spectroscopy on liquid water, 59,60 thermoacoustic effects dominate. In first approximation, the absorption triggers thermal expansion that, in turn, can induce a pressure wave with associated mass displacement and density perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Optoacoustic effects originate from the fact that the optical properties of a medium can change as a result of density variations, 62 which can trigger the generation of acoustic waves. [70][71][72][73][74][75][76] When radiation is strongly absorbed, as in the case of Terahertz spectroscopy on liquid water, 59,60 thermoacoustic effects dominate. In first approximation, the absorption triggers thermal expansion that, in turn, can induce a pressure wave with associated mass displacement and density perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous literature, asymmetric SEM tensors have been introduced [76], but in our work, all SEM tensors are symmetric and strictly based on the classical definition in Eq. (37). We require that the SEM tensors of the total system and its subsystems, e.g., the material and field+interaction subsystems, must all transform between inertial frames in a relativistically covariant way.…”
Section: Stress-energy-momentum Tensorsmentioning
confidence: 99%
“…Experimental studies of electrostriction have also revealed interesting phenomena, such as the giant electrostriction [15][16][17][18][19][20][21][22][23][24][25], negative electrostriction [26,27], and deformations of liquid crystals [28,29] and biological cells [30]. On the theoretical side, electrostriction has also been under extensive study [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was theoretically demonstrated that the electrostrictive forces induced by the laser in liquid could be the source of acoustic pulses [8,9]. In another example the volumetric ponderomotive force occurs when a high voltage is rapidly applied to a sharp needle-like electrode produce region with significant negative pressure leading to the rupture of liquid, i.e.…”
Section: Introductionmentioning
confidence: 99%